Real-time PCR genotyping using displacing probes - Cheng, Jinping (Oxford University Press, 2004)
Simple and reliable genotyping technology is a key to success for high-throughput genetic screening in the post-genome era. Here we have developed a new real-time PCR genotyping approach that uses displacement hybridization-based probes: displacing probes. The specificity of displacing probes could be simply assessed through denaturation analysis before genotyping was implemented, and the probes designed with maximal specificity also showed the greatest detection sensitivity. The ease in design, the simple single-dye labeling chemistry and the capability to adopt degenerated negative strands for point mutation genotyping make the displacing probes both cost effective and easy to use. The feasibility of this method was first tested by detecting the C282Y mutation in the human hemochromatosis gene. The robustness of this approach was then validated by simultaneous genotyping of five different types of mutation in the human β-globin gene. Sixty-two human genomic DNA samples with nine known genotypes were accurately detected, 32 random clinical samples were successfully screened and 114 double-blind DNA samples were all correctly genotyped. The combined merits of reliability, flexibility and simplicity should make this method suitable for routine clinical testing and large-scale genetic screening.